2016
DOI: 10.1016/j.str.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Binding Drives Catalytic Activation of Aminoglycoside Kinase APH(2″)-Ia

Abstract: APH(2″)-Ia is a widely disseminated resistance factor frequently found in clinical isolates of Staphylococcus aureus and pathogenic enterococci, where it is constitutively expressed. APH(2″)-Ia confers high-level resistance to gentamicin and related aminoglycosides through phosphorylation of the antibiotic using guanosine triphosphate (GTP) as phosphate donor. We have determined crystal structures of the APH(2″)-Ia in complex with GTP analogs, guanosine diphosphate, and aminoglycosides. These structures collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 59 publications
(73 reference statements)
2
18
0
Order By: Relevance
“…Other than the linker, the topology of MPH(2 0 )-I and MPH(2 0 )-II closely resembles that of the APH(2 00 ) enzymes, with which they share approximately 17% sequence identity ( Figure 1C) (Caldwell et al, 2016). The apo MPH(2 0 )-II structure is less well defined than that of MPH(2 0 )-I.…”
Section: Resultsmentioning
confidence: 91%
“…Other than the linker, the topology of MPH(2 0 )-I and MPH(2 0 )-II closely resembles that of the APH(2 00 ) enzymes, with which they share approximately 17% sequence identity ( Figure 1C) (Caldwell et al, 2016). The apo MPH(2 0 )-II structure is less well defined than that of MPH(2 0 )-I.…”
Section: Resultsmentioning
confidence: 91%
“…APH enzymes are structurally related to the catalytic domains of the eukaryotic protein kinases (Hon et al, 1997), particularly with respect to the nucleotide-binding site and the anchoring of the triphosphate moiety. However, unlike protein kinases, the phosphoryl-transfer reaction of which is tightly regulated (Johnson et al, 1996(Johnson et al, , 1998Endicott et al, 2012), the APH enzymes are deemed to be essentially unregulated since they lack most of the kinase regulatory machinery (Davies & Wright, 1997;Caldwell et al, 2016). For some APH enzymes it has been demonstrated that apart from their major function, the phosphorylation of aminoglycosides, they continuously hydrolyze bound NTPs in the absence of the antibiotic substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Recent structural studies with APH(2 00 )-Ia suggest that in this particular enzyme nucleotide hydrolysis may be regulated by conformational changes (Caldwell et al, 2016). In the absence of aminoglycoside antibiotics, the triphosphate moiety of the bound GTP is held in a stabilized, inactive state and it is likely that in this state adventitious hydrolysis and transfer of the -phosphate to water may be minimized.…”
Section: Introductionmentioning
confidence: 99%
“… In a recent issue of Structure , Caldwell et al (2016) determined crystal structures of APH(2″)-Ia in complex with various combinations of aminoglycosides and nucleosides, which compellingly revealed that the catalytic activity of this resistance enzyme is regulated by a conformational change of the triphosphate of GTP, a mechanism previously unknown for antibiotic kinases. …”
mentioning
confidence: 99%
“…Thanks to the masterful structural biology studies of Berghuis and coworkers, this knowledge gap has now been filled (Caldwell et al, 2016). Through rigorous evaluation of ten different crystal structures of APH(2″)-Ia in complex with various combinations of AGs and cofactors, the authors have finally “shone a light” on APH(2″)-Ia and unraveled a sophisticated regulatory mechanism (Figure 1).…”
mentioning
confidence: 99%